2004
DOI: 10.1017/s003329170400203x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of beliefs about mental health problems and coping on outcome in schizophrenia

Abstract: These results suggest that the SRM is a promising model for mental health problems and may highlight important areas for development in clinical, and especially psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 23 publications
(18 reference statements)
9
72
1
2
Order By: Relevance
“…The mean age of the sample was 26 years old (s.d. = 4.40, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and 70% (n = 57) were male. All participants met the eligibility criteria for the EIS and therefore met the inclusion criteria for the study: all participants were aged 18-35; had been in contact with the EIS for between 1 and 3 years (range 12-34 months, mean = 19.42, s.d.…”
Section: Participantsmentioning
confidence: 99%
“…The mean age of the sample was 26 years old (s.d. = 4.40, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and 70% (n = 57) were male. All participants met the eligibility criteria for the EIS and therefore met the inclusion criteria for the study: all participants were aged 18-35; had been in contact with the EIS for between 1 and 3 years (range 12-34 months, mean = 19.42, s.d.…”
Section: Participantsmentioning
confidence: 99%
“…McGlashan (1987) found that recovery style was an important predictor of "global outcome," which included symptoms and functioning. (Leventhal, Nerenz, & Steele, 1984) such as beliefs about the degree to which one has a problem, the consequences of having a mental illness, and degree of personal control, were relevant to understanding how people with schizophrenia make sense of their experience and choose to cope (Lobban et al, 2003;Lobban, Barrowclough, & Jones, 2004). Specifically, the authors found that individuals who believed that that they had greater personal control over symptoms tended to use more "positive" coping strategies.…”
Section: Cognitive Appraisal and Copingmentioning
confidence: 99%
“…IP is defined as the self-definition of health status influenced by illness-related experiences in the past [11]. Originally developed in the physical health area, IP has recently been applied to individuals with mental disorders [12,13,14,15], their relatives [16], and mental health practitioners [17]. Crisp et al [18] found that patients think differently about specific diagnoses, indicating the need for distinct assessment methods of IP.…”
Section: Introductionmentioning
confidence: 99%